2009
DOI: 10.1590/s0034-72802009000100009
|View full text |Cite
|
Sign up to set email alerts
|

Retinal nerve fiber layer loss documented by optical coherence tomography in patients with optic tract lesions

Abstract: Purpose: To report abnormalities of retinal nerve fiber layer (RNFL) thickness using Stratus -optical coherence tomography (OCT) in two patients with optic tract lesions. Methods: Two patients with long standing homonymous hemianopia from optic tract lesions were submitted to a complete neuro-ophthalmic evaluation and to Stratusoptical coherence tomography examination. Results: Both patients revealed diffuse loss of the RNFL at Stratus -OCT in both eyes. In the eyes with the temporal hemianopia, RFNL loss was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
1
0
1
Order By: Relevance
“…OTL is a relatively rare clinical entity, and previous publications present case series with various etiologies as summarized in Table 1 . Monteiro and Hokazone ( 22 ) described two cases in young patients, one due to trauma and the other a diagnosed tumor. Kanamori et al ( 23 ) reported trauma, arterio-venous malformation, and two cases of malignancy resulting in right homonymous hemianopia due to left OTL.…”
Section: Discussionmentioning
confidence: 99%
“…OTL is a relatively rare clinical entity, and previous publications present case series with various etiologies as summarized in Table 1 . Monteiro and Hokazone ( 22 ) described two cases in young patients, one due to trauma and the other a diagnosed tumor. Kanamori et al ( 23 ) reported trauma, arterio-venous malformation, and two cases of malignancy resulting in right homonymous hemianopia due to left OTL.…”
Section: Discussionmentioning
confidence: 99%
“…(86) No olho da hemianopsia nasal evidenciou-se a perda de fibras nos quadrantes superior e inferior do disco óptico, acometendo, portanto, as fibras da retina temporal que penetram o olho pelas arcadas superior e inferior. Os casos serviram para confirmar o valor da TCO na identificação da perda neural nestes pacientes.…”
Section: Lesões Do Trato óPtico E Corpo Geniculado Lateralunclassified